IMPACT OF COVID-19 ON BORDER GUARDS TRAINING IN LATVIA, LITHUANIA, ESTONIA AND FINLAND. - Spridzans, Martins; Dzerviniks, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Due to Covid-19 the use of educational technologies, efficient and meaningful implementation of digital learning possibilities have become particularly important topics in order to develop border guards training. Issues related to training online, communication via several platforms, possibilities do develop interactive training content, need to use the potential of e-learning opportunities have become routine topics of discussion and ongoing research. Trainers of border guard training institutions have to tackle unexpected, unexplored, challenges and tasks related to border guards training due to Covid-19. Digital competence is particularly important to implement efficient online communication environment. To find out training and learning outcomes and define further necessities of e-learning development during emergency situations the authors of this research explore the scientific literature on the current research results, methodologies, approaches and best practices on developing e-learning systems in educational contexts during Covid-19. Survey results on attitudes, experiences and suggestions of border guards’ trainers in Latvia, Lithuania, Estonia and Finland have been analysed to put forward suggestions for further border guard training development particularly in e-learning context during emergency situations.